First Report on Natural Promastigote Infection of Phlebotomus caucasicus in a New Focus of Visceral Leishmaniasis in North West of Iran - Y Rassi; F Kaverizadeh; E Javadian; M Mohebali (Iranian Journal of Public Health, 2004)
An investigation was carried out in Ahar district, (a new focus of visceral leishmaniasis), Eastern Azerbaijan, North-West of Iran in order to determine the vector(s) of the disease, during the summer of 2003 sand-flies were collected using sticky papers, CDC light traps and aspirators. All of the collected sand-flies were dissected in a drop of normal saline for surveying of promastigotes. Head and two last abdomen segments of-sandflies were mounted in a drop of Puri’s Medium for species identification. Totally 215 sandflies were collected including: Phlebotomus kandelakii (57.2%), P.perfiliewi (18.1%), P.caucasicus (11.2%), P. sergenti (7.9%), P. papatasi (3.3%) and P.(adlerius) sp.(2.3%). Only 1 of 24 P. caucasicus species (4.2%) was found naturally infected with parasite. This is the first infection report of P. caucasicus in this region. Some behavioral aspects of the mentioned sandfly have been discussed in details.